2020
DOI: 10.1073/pnas.1916244117
|View full text |Cite
|
Sign up to set email alerts
|

Division of labor and growth during electrical cooperation in multicellular cable bacteria

Abstract: Multicellularity is a key evolutionary innovation, leading to coordinated activity and resource sharing among cells, which generally occurs via the physical exchange of chemical compounds. However, filamentous cable bacteria display a unique metabolism in which redox transformations in distant cells are coupled via long-distance electron transport rather than an exchange of chemicals. This challenges our understanding of organismal functioning, as the link among electron transfer, metabolism, energy conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 43 publications
16
93
0
2
Order By: Relevance
“…The cell specific oxygen consumption rate of cable bacteria in the oxic zone calculated from the cathodic oxygen consumption, the oxygen penetration depth (∼1 mm; Figure 1E ) and qPCR enumerated cable bacteria is 69 ± 58 fmol O 2 cell –1 day –1 , which is within the same order of magnitude as the value of 36 fmol O 2 cell –1 day –1 reported by Schauer et al (2014) . Measurements of the oxygen reduction capacity of cable bacteria using cyclic voltammetry resulted in a rate of 6.1 pmol O 2 cell –1 day –1 (at 50 μM O 2 ; Geerlings et al, 2020 ), hence the potential capacity for oxygen reduction is approximately a hundred times larger than the actual rates in sediment incubations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell specific oxygen consumption rate of cable bacteria in the oxic zone calculated from the cathodic oxygen consumption, the oxygen penetration depth (∼1 mm; Figure 1E ) and qPCR enumerated cable bacteria is 69 ± 58 fmol O 2 cell –1 day –1 , which is within the same order of magnitude as the value of 36 fmol O 2 cell –1 day –1 reported by Schauer et al (2014) . Measurements of the oxygen reduction capacity of cable bacteria using cyclic voltammetry resulted in a rate of 6.1 pmol O 2 cell –1 day –1 (at 50 μM O 2 ; Geerlings et al, 2020 ), hence the potential capacity for oxygen reduction is approximately a hundred times larger than the actual rates in sediment incubations.…”
Section: Resultsmentioning
confidence: 99%
“…The pathway by which oxygen is reduced in cable bacteria is currently unknown. Recent 13 C and 15 N labeling studies have shown that cells in the oxic zone of the sediment show very little or no carbon or nitrogen assimilation, implying that oxygen reduction in cable bacteria is not coupled to energy conservation (Geerlings et al, 2020). Moreover, no terminal oxidases could be identified in cable bacteria genomes and it was hypothesized that cable bacteria reduce oxygen via periplasmic cytochromes (Kjeldsen et al, 2019).…”
Section: Metabolic Activity Of Cable Bacteria At the Single Filament mentioning
confidence: 99%
“…Cable bacteria were observed to generate distinct distortions of the oxic-anoxic interface in gradient systems, and we realized that this allowed measurements of the rate and location of oxygen consumption in individual bacteria. This novel approach was used in the present study to directly test the hypothesis that cable bacteria can limit oxygen reduction to a few cells with high consumption rates (10,12). Data from independent individuals of a single-strain population established in seminatural gradient systems were collected until robust measures of the variability and biomass-specific capacity of oxygen consumption were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Division of labor allows populations of individuals to more efficiently carry out functions that are mutually incompatible 25,26 . In microbes, division of labor can facilitate biofilm formation 25,27,28 , energy transfer 29 , and coordinated metabolism 13,30 , among other behaviors. In some cases, division of labor leads to sub-populations of cells that carry out functions that are lethal to themselves but that benefit the entire colony 31 .…”
Section: Discussionmentioning
confidence: 99%